Difference between revisions of "Substitute Command"

From GeoGebra Manual
Jump to: navigation, search
(command syntax: changed [ ] into ( ))
(Remove overly complicated example)
 
Line 4: Line 4:
 
:Substitutes ''from'' in ''expression'' with ''to''.
 
:Substitutes ''from'' in ''expression'' with ''to''.
 
:{{examples| 1=<div>
 
:{{examples| 1=<div>
:*<code><nowiki>Substitute((x^2 / (4x + 6))^2 + 6(x^2 / (4x + 6)) + 8, x^2, a*(4x + 6))</nowiki></code> yields ''a<sup>2</sup> + 6 a + 8''.
 
 
:*<code><nowiki>Substitute((3 m - 3)^2 - (m + 3)^2, m, a)</nowiki></code> yields ''8 a<sup>2</sup> - 24 a''.</div>}}
 
:*<code><nowiki>Substitute((3 m - 3)^2 - (m + 3)^2, m, a)</nowiki></code> yields ''8 a<sup>2</sup> - 24 a''.</div>}}
 
;Substitute( <Expression>, <Substitution List> )
 
;Substitute( <Expression>, <Substitution List> )
 
:Substitutes in ''expression'' every variable of the list with the variable or number you choose for it.
 
:Substitutes in ''expression'' every variable of the list with the variable or number you choose for it.
 
:{{example| 1=<code><nowiki>Substitute(2x + 3y - z, {x = a, y = 2, z = b})</nowiki></code> yields ''2a - b + 6''.}}
 
:{{example| 1=<code><nowiki>Substitute(2x + 3y - z, {x = a, y = 2, z = b})</nowiki></code> yields ''2a - b + 6''.}}

Latest revision as of 11:50, 11 January 2024


CAS Syntax

Substitute( <Expression>, <from>, <to> )
Substitutes from in expression with to.
Examples:
  • Substitute((3 m - 3)^2 - (m + 3)^2, m, a) yields 8 a2 - 24 a.
Substitute( <Expression>, <Substitution List> )
Substitutes in expression every variable of the list with the variable or number you choose for it.
Example: Substitute(2x + 3y - z, {x = a, y = 2, z = b}) yields 2a - b + 6.
© 2024 International GeoGebra Institute